Biological Aspects of Three Species Family Gobiidae in the Bilah River, Labuhanbatu Regency, Sumatera Utara Province - Khairul, Khairul; Lubis, Ika Nazira (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
The Bilah river is known to have a fairly high fish biodiversity. Some species of Gobiidae are usually caught by fishermen in the estuary area. But until now there is no data and information related to the biological aspects of the Gobiidae family. The purpose of this study was to determine aspects of the size class and long relationship of the weight of Gobiidae fish caught by fishermen in the Bilah river. This study is exploratory, where fish sampling stations are determined based on fish habitat from fishermen's information (purposive sampling). Fish are caught using traditional fishing gear in the form of splint. The fish caught is then measured in total length and weight. Then the fish obtained based on the catch are grouped in small, medium, and large sizes. Data analysis using Microsoft Excel 2010 applications. In this study, three species of fish that are included in the family Gobiidae namely Butis butis, Butis aureus, and Eleotris fusca. The small category B. butis (9-11.9 cm) fish size class is obtained as many as 2 individuals, medium size (12-14.9 cm) 9 individuals, and large size (15-17.9 cm) 2 individuals. The small size class (6-8.9 cm) of B. aureus fish obtained 2 individuals, medium (9-11.9 cm) 8 individuals, and large 12-14.9 cm) 4 individuals. Small size class (9-11.9 cm) E. fusca as many as 6 individuals, medium (12-14.9 cm) 7 individuals, and large (15-17.9 cm) 3 individuals. The growth pattern of the crazy fish (B. butis) (value b = 0.10), B. aureus (value b = 0.27), and E. fusca (value b = 0.20).